Kompetensi Pustakawan Zaman Now - Sarwono . (LIBRARIA : Jurnal Ilmu Perpustakaan dan Informasi, 2018)
Perpustakaan semakin berkembang seiring perkembangan zaman. Berbagaimacam perubahan yang terjadi di perpustakaan antara lain perubahankoleksi, pemustaka dan perubahan layanan. Pemustaka saat mini didominasioleh generasi y, generasi z dan bahkan generasi alfa. Pustakawan yang adasaat ini terdiri dari beberapa generasi. Sehingga pustakawan perlu berubahmenyesuaikan diri dengan perubahan tersebut. Kompetensi pustakawan harusditingkatkan. Kompetensi pustakawan yang harus dimiliki pustakawanzaman now antara lain: kompetensi teknologin informasi, kompetens bahasaasing, kompetensi psikologi, kompetensi komunikasi. Dengan meningkatnyakompetensi pustakawan diharapkan mereka dapat mmemberikan pelayananterbaik kepada pemustaka zaman now. ---------------------------------------------------- The library has now rapidly developed throughout the time. Several changes takeplace such as the collection shift, the librarian, and the change of their service.The librarians now are predominantly dominated by y generation, z generation,and even alpha generation. The librarians presently consist of different generations.Thus, the librarians subsequently need to adjust to the changing situation.They have to improve their competence. The competences that the librarians ofZaman Now must have are such as: information technology, foreign languageskill, psychology, and communication competence. As their capability on thoseskills increase, it is expected that they could give the best service to the libraryvisitors of Zaman Now.